SPAC3: space for art (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
In both the scientific as well as the humanistic domains, the verbal dimension plays a pri mary role compared to the visual one. However, science has made significant steps forward thanks to informative or evocative imagery. Indeed, the history of scientific achievements has been punctuated by its iconographic content, and communication through images contributes to successful dissemination of important scientific discoveries. In the space domain, meaningful images have left a mark in the collective memory both for being brand−new and for their highly symbolical nature. Today, the space photos taken by the astronaut Paolo Nespoli and made available to the public by the European Space Agency (ESA)1, have become the main ingredient of a social work of art thanks to the Third Paradise symbol by Michelangelo Pistoletto. An art project that joins together the world of science to that of art in both a modern and inclusive way.